2015
DOI: 10.1016/j.leukres.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Increased likelihood of post-polycythemia vera myelofibrosis in Ph-negative MPN patients with chromosome 12 abnormalities

Abstract: Chromosome 12 (Chr12) abnormalities have been described for individual patients with Philadelphia chromosome-negative myeloproliferative neoplasms (Ph-neg MPN), however the frequency, characteristics, and outcomes of such patients as a whole have not been investigated. We reviewed a database of 1787 consecutive Ph-neg MPN patients seen at our institution and determined that 2% of Ph-neg MPN patients harbored an alteration involving Chr12 by cytogenetic evaluation. Retrospective chart review revealed that patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…Molecular indicators of fibrotic progression from PV are not well characterized. Some evidence exists suggesting an association between chromosome 12 abnormalities and an increased risk of developing post-PV MF [ 176 ]. Evidence also exists to support a significantly higher JAK2 V617F allelic frequency [ 11 , 83 , 131 , 137 , 176 ] or a progressive increase [ 177 ] in patients who transform to SMF.…”
Section: Prognosismentioning
confidence: 99%
“…Molecular indicators of fibrotic progression from PV are not well characterized. Some evidence exists suggesting an association between chromosome 12 abnormalities and an increased risk of developing post-PV MF [ 176 ]. Evidence also exists to support a significantly higher JAK2 V617F allelic frequency [ 11 , 83 , 131 , 137 , 176 ] or a progressive increase [ 177 ] in patients who transform to SMF.…”
Section: Prognosismentioning
confidence: 99%
“…Preliminary evidence suggests that chromosome 12 abnormalities are associated with a greater likelihood to progress to PPV-MF. 27 Occurrence of PPV-MF signifies a dramatic shortening of PV survival to a median of approximately six years with an adjusted hazard ratio (HR) of 2.17. 26 A longer (>10 years) duration of the chronic PV phase is also associated with shortened survival after transformation to PPV-MF (HR 2.26).…”
Section: Diagnosis Of Transformation To Post-polycythemia Vera Myelofmentioning
confidence: 99%
“…It has been reported that older age, leukocytosis, splenomegaly, thrombocytosis, a masked-PV phenotype (PV characteristics with lower hemoglobin levels than criteria targets), a high JAK2 V617F allele burden, and chromosome 12 abnormalities are associated with the evolution of MF in PV ( 16 , 36 ). Among these factors, only old age and splenomegaly fit our case, and the cause of his MF evolution remains unknown.…”
Section: Discussionmentioning
confidence: 99%